{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

lecture_15

# lecture_15 - MIT OpenCourseWare http/ocw.mit.edu 2.004...

This preview shows pages 1–4. Sign up to view the full content.

MIT OpenCourseWare http://ocw.mit.edu 2.004 Dynamics and Control II Spring 2008 For information about citing these materials or our Terms of Use, visit: http://ocw.mit.edu/terms .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
i n K 9 ± ± G J B J 9 ± ± f r i c t i o n a l d r a g p l a t e s Massachusetts Institute of Technology Department of Mechanical Engineering 2.004 Dynamics and Control II Spring Term 2008 Lecture 15 1 Reading: Class Handout: Modeling Part 1: Energy and Power Flow in Linear Systems Sec. 3. Class Handout: Modeling Part 2: Summary of One-Port Primitive Elements Nise: Secs. 2.4 and 2.6. 1 Rotational Systems (continued) Example 1 The diagram shows a mechanical tachometer that uses frictional drag plates to create a torque proportional to angular velocity difference. The angular velocity is indicated by the displacement θ of a torsional spring. Find the transfer function relating the displacement of the indicator θ to the input angular velocity Ω in θ ( s ) H ( s ) = Ω in ( s ) and show that for a constant input angular velocity the steady-state indicated speed θ ss Ω i . Solution: There are two distinct angular velocities, and the system graph is: 1 copyright c D.Rowell 2008 15–1
J B K 9 = 0 i n 9 ± ± a c r o s s - v a r i a b l e s o u r c e Using impedances, redraw the graph combining the inertia and the spring into a single impedance Z 2 : Z Z 9 = 0 i n 9 ± ± J 9 ± ± 1 2 T Z = 1 1 B 1 Z = 2 1 J s s K = 1 / J K s / K + 1 / J s Then Z 2 Ω J = Ω in ( s ) Z 1 + Z 2 s/ ( Js 2 + K ) = Ω in ( s ) 1 /B + s/ ( Js 2 + K ) Bs = Ω in ( s ) . Js 2 + Bs + K But the angular displacement θ ( s ) = Ω J ( s ) /s so that B H ( s ) = Js 2 + Bs + K If the input velocity is a step function at t = 0, the Ω in ( s ) = Ω /s and the steady-state indicated value will be Ω B θ ss = lim θ ( t ) = lim ( s ) = lim sH ( s ) = Ω t →∞ s 0 s 0 s K show that

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}